2018
DOI: 10.1016/j.jdent.2017.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Topical silver diamine fluoride for dental caries arrest in preschool children: A randomized controlled trial and microbiological analysis of caries associated microbes and resistance gene expression

Abstract: The treatment is applicable to primary care practice and may reduce the burden of untreated tooth decay in the population.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
2
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 38 publications
5
75
2
5
Order By: Relevance
“…Most of the genera present before the intervention (Olsenella, Streptococcus, Bifidobacterium, Prevotella_7, Lactobacillus, Actinomyces, Leptotrichia, Selenomonas_3, Veillonella) were sensitive to SDF, and the relative amounts decreased substantially. This was consistent with previous studies [15,16,18,20] and supported the broad spectrum bactericidal effect of SDF [25]. Streptococcus,…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Most of the genera present before the intervention (Olsenella, Streptococcus, Bifidobacterium, Prevotella_7, Lactobacillus, Actinomyces, Leptotrichia, Selenomonas_3, Veillonella) were sensitive to SDF, and the relative amounts decreased substantially. This was consistent with previous studies [15,16,18,20] and supported the broad spectrum bactericidal effect of SDF [25]. Streptococcus,…”
Section: Discussionsupporting
confidence: 93%
“…The antimicrobial effect of SDF has been proven by various previous studies [15][16][17][18][19][20]25], but the effect of SDF on micro-ecology of dental plaque has seldom been explored. Based on the already known antimicrobial effect of SDF, this pioneer preliminary study aimed to further our knowledge of SDF on dental plaque from the micro-ecosystem aspect.…”
Section: Discussionmentioning
confidence: 99%
“…Another study of preschool children looked at both the impact of 38% SDF on arrest rates and resulting changes in the plaque flora. 232 Similar to related studies, caries arrest was confirmed, but the RNA sequencing of microbes indicated that there was no change in the relative abundance of caries-associated microbes after treatment. While the treatment did not appear to alter the plaque flora, it also did not lead to the emergence of antibiotic or metal-resistant gene expression in the organisms.…”
Section: Silver Diamine Fluoridesupporting
confidence: 77%
“…As SDF exerts such a strong antibacterial activity, it has been feared that topical treatments would dramatically reduce diversity and thereby enable growth of unwanted, opportunistic pathogens. In contrast to the expectations, MILGROM and coworkers (44) found no significant loss of species diversity and no changes in the relative abundance of bacteria associated with dental caries after topical application of SDF. The findings need to be validated in larger settings but the authors concluded that SDF treatment seemed to pose a minimal risk of unintended systemic effects on the oral microbiome (44).…”
Section: Antibacterial Strategiesmentioning
confidence: 70%